Analysis of wear on abrasive water jet nozzle - Izzudin, Nazar (2016)
An abrasive water jet (AWJ) system is a manufacturing tool that uses high pressure (200-400 MPa) water to accelerate abrasive particles through a carbide nozzle they are eroding a target material. Nozzle wear is dependent on the numerous AWJ system and nozzle parameters such as water pressure, orifice diameter, abrasive type, abrasive size, abrasive shape, abrasive flow rate, and mixing chamber dimensions. The present study investigates the wear profile of the nozzle. The nozzles are made from tungsten carbide. They experienced normal wear after standard use between 100 to 120 hours. The roundness of the AWJ nozzle can be seen after the machining process and the roundness can be more resistant to the chipping and damage if the radius of AWJ nozzle is small. For wear profile, the result shows that the nozzle number 1 has bigger diameter at the entranced which are 4.28 mm compared to nozzle number 2 that the diameter are 4.07 mm. Then, the wave structure grows in magnitude and propagates down the nozzle bore. The wear patterns were observed, which are the converged wear pattern occurred at the bore of the AWJ nozzles. From the result, the erosion mechanism that occurs in the AWJ nozzles can be divided into three stages which are an inlet, middle and outlet, and the highest erosion mechanism occured in the inlet area. The wear of the AWJ nozzle can occur through the systematic variation of the system parameters AWJ and the nozzle geometry.